The Difficult Choice of "Not Doing"; Comment on "Quaternary Prevention, an Answer of Family Doctors to Overmedicalization" - Giorgio Visentin (Kerman University of Medical Sciences, 2015)
The article of Marc Jamoulle shows the importance of the contribution of general practitioners (GPs) in improving the quality and the efficiency of the health systems. Starting from the concept of quaternary prevention for reducing excessive costs in the preventive procedures, he suggests a change of paradigm in every daily activity of the GP in order to have a stronger ethical approach to the patient. This means spending more time in the consultation in order to better understand her/his real needs and share a common decision for minimizing the costs and solving the patient's problems in agreement with her/his believes and values.